Pediatric Acute Care Simulator Case: Supraventricular Tachycardia - Mark Adler; Jennifer Trainor; Viva Jo Siddall; William McGaghie (Association of American Medical Colleges, 2009)
Abstract This work is one of a series of four pediatric simulation cases developed as part of a performance evaluation research project. The case consists of a case scenario in which a 6-year-old has fallen from his bike and has an obvious leg deformity. This material would be useful for formative evaluation of pediatric residents or as part of a larger set of cases for medium-stakes summative evaluation (e.g., end-of-year performance assessment in a residency program). The publication reviews the validation data. The instruments proved both reliable and valid for our subject audience (pediatric residents). Checklist rating instruments are a commonly used approach for simulation-based assessment, in part because they can produce highly reliable ratings if the raters are well trained and the instrument is fine-tuned. However, checklists are time-insensitive and may not match a more general/global assessment of a subject's performance. For example, a very slow methodical subject would achieve an identical checklist score to a highly efficient performance using these tools.